Trends in self-rated health among the elderly population in Germany from 1995 to 2015 - the influence of temporal change in leisure time physical activity - Stefanie Sperlich; Johannes Beller; Jelena Epping; Juliane Tetzlaff; Siegfried Geyer (BMC, 2020)
Abstract Background Against the backdrop of rising statutory retirement age in Germany, we analyzed time trends in self-rated health (SRH) among the elderly population between 50 and 70 years of age and explored the mediating role of leisure time physical activity (LTPA) on the relationship between time period and self-rated health (SRH). Methods We used longitudinal survey data (n = 23,161) from a national panel study (GSOEP) to analyze time trends in SRH and regular LTPA (at least once a week) by means of Generalized Estimation Equation (GEE) analysis for logistic regression. The Karlson-Holm-Breen (KHB) method was applied for decomposing trend effects into direct and indirect parts via LTPA. In addition to odds ratios (OR), we illustrated the results by means of predicted probabilities and average partial effects (APE). Results Over time, the predicted probabilities of good SRH and regular LTPA increased while those of poor SRH decreased. After adjusting for socioeconomic status (SES) 53.4% of the trend in good SRH in women (OR = 1.34 / APE = 6.8%-points) could be attributed to the rise in regular LTPA. In men, the remaining smaller effect (OR = 1.13 / APE = 2.7%) could be fully assigned to temporal changes in regular LTPA. With respect to poor health we found a suppression effect of LTPA in the adjusted model, indicating that without improvements in regular LTPA over time an increase in poor SRH would have occurred. Conclusions The increase of regular LTPA accounted for improved SRH from 1995 to 2015 among the elderly, indicating that promoting LTPA might be a key factor to raise healthy working life expectancy.